Exploring the Effects of Social Media Usage on Peer Relationship among College Students - Rashid, Rabia; Bajwa, Muhammad Jamil; Naeemullah, Muhammad (Annals of Human and Social Sciences, 2024)
Social media has become a central aspect of college students' lives, significantly influencing how they interact and maintain peer relationships. This study aimed to investigate the comparative effects of social media use on peer relationships among male and female college students in Islamabad. The objectives of the study were: to find out, investigate and compare the effect of social media usage on male and female college students of Islamabad. The sample of 71 students (54 female and 17 male) from different colleges were selected randomly and data was collected by using a questionnaire. Data were tabulated and results showed that use of social media platforms had significant effects on self-esteem and peer relationships among college students. The study suggested that awareness campaigns could help students to use social media in a positively controlled ways.